Artificial Intelligence in the Management of Obesity - Khushboo Agarwal (Indian Journal of Endocrinology and Metabolism)
The prevalence of obesity has increased significantly in the last few years. Addressing obesity needs multifaceted strategy including prevention, accurate diagnosis, treatment of secondary causes, diet and exercise, behavioral changes and long term management. In addition it involves integration of multiple teams including endocrinologist, respiratory medicine, ENT, psychiatry, physiotherapy, diet, and bariatric surgeon. Artificial intelligence can help with each of these aspects by enabling predictive analysis, behavioral intervention in real time and improving patient outcome. There are certain challenges in integrating AI with patient management including ensuring data privacy and mitigating algorithm bias. But overall, it represents a promising tool to empower both the individual and the physician treating obesity.